Moderasi Keberagamaan dan Nilai Sosial Dalam Pemikiran Mukti Ali - Derry Ahmad Rizal; Slamet Maksun; Ernah Dwi Cahyati (Kopertais Wilayah III Yogyakarta, 2021)
This article aims to describe the religious moderation that exists in Indonesia with the perspective of Mukti Ali's thoughts. In this article method, it uses library research. The understanding of religious moderation conveyed in Mukti Ali's thinking, harmony, and harmony that exist in society are the basic values that must be possessed by everyone. As it becomes a basic value that every society must have, it will foster social values in religion. The conclusion of this article is that Indonesian society has not fully applied the understanding of religious moderation. Field evidence shows that there are several cases that occur in Indonesia on behalf of certain religious groups. This requires a re-evaluation of the understanding or implementation of the value of religious moderation. Keyword: Moderasi Beragama, Mukti Ali, Sosial